Pengaruh Penambahan Jamur Kuping Hitam (Auricularia Polytricha) Terhadap Sifat Kimia dan Organoleptik Nugget Ikan Tongkol Abu-Abu (Thunnus Tonggol) - Dheniawan Danu Sukma Tirta Suradiyanto; Dyah Ilminingtyas Wahyu Handayani (Jurnal Agrifoodtech, 2023)
Fish nuggets are a food that is quite popular with people because they contain high nutrition. Addition of black ear mushrooms to gray tuna nuggets to increase nutritional value and crude fiber content and acceptability. This study aims to determine the effect of the correct concentration of black ear fungus on chemical and organoleptic properties. This research was conducted using a completely randomized design method (CRD) with 4 treatments at the concentration of addition of black ear fungus 0% (K0) as a control, 10% (K1), 20% (K2), 30% (K3) of 100 g tuna. gray with 3 repetitions. The results of the chemical properties research showed that the water content ranged from 42.50% -51.00%. The best treatment was obtained (K3) of 51.00% fulfilled the SNI with a maximum of 60%, ash content was 2.63% -2.98%. K1) of 2.63% does not meet SNI with a maximum of 2.5%, protein content of 13.76% -15.31%, the best treatment is obtained (K0) of 15.31% meets SNI at least 5%, fat content is 13.22 % -15.25% obtained the best treatment (K3) of 13.22% fulfilling SNI with a maximum of 15%, crude fiber 0.22% -0.70% obtained the best treatment (K3) of 0.70%. The results of the organoleptic analysis regarding the taste of fish nuggets were 5.04-5.64 on average, the best treatment was obtained (K1) 5.64 (likes), the aroma was 4.68-5.32, the best treatment was obtained (K1) 5.32 ( rather like), texture 5.00-5.32 obtained the best treatment (K1) 5.32 (rather like), color 4.92-5.36 obtained the best treatment (K1) 5.36 (rather like).